Moluscos encontrados no Sambaqui de Camboinhas, Itaipu, Niterói, estado do Rio de Janeiro, Brasil Mollusca found in the Camoinhas' kitchen midden, Itaipu, Niterói, Rio de Janeiro State - Elisa Maria Botelho de Mello; Arnaldo C. dos Santos Coelho (Memorias do Instituto Oswaldo Cruz, 1989)
Archaelogical aspects of Camboinhas' kitchen midden, Itaipu, Niterói, Rio de Janeiro State are presented, as well as samples of mollusca species found in the kitcheen midden.